Analisis Perbandingan Tingkat Tekanan Bunyi Terhadap Sistem Pembangkit Suara Akustik dengan Efek Surround dan Tanpa Efek Surround - Yusuf Nugraha (Universitas Indraprasta PGRI Jakarta, 2020)
This study aims to determine the comparison of the sound pressure level produced by an acoustic sound generator system with surround effects without surround effects. Acoustic sound generating system with surround effects is designed and made as a sound system that produces a surround effect where the resulting sound is divided and distributed over two or many channels (multi channel). This sound system consists of four parts, namely: front cannel, rear surround channel, extra rear channel and subwoofer. This system gets input from the VCD in the form of R and L signals into the AN7397K IC then comes out through four output channels. Each output channel is connected to a 150 watt stereo and mono power amplifier. From the results of research with statistical tests using the t distribution shows that there is a difference in sound pressure level (SPL) between acoustic sound generating systems with surround effects without surround effects at a distance of 1 meter to 10 meters, where the value of the sound pressure level with a sound generator system is obtained. acoustics with a surround effect higher than the sound pressure level without a surround effect